Biomarcadores moleculares en mastitis bovina - Caggiano, N. (2021)
Mastitis is an inflammation of the mammary gland generally caused by a bacterial infection. It is the disease that has the highest morbidity and mortality within dairy herds, affecting milk production and the profitability of the dairy farms. Besides, if the process is severe or prolonged, it often causes irreversible damage to the mammary gland. In addition to the somatic cell count and profile protein analysis, the evaluation of molecular markers related to inflammation is of interest for the early diagnosis, control and prognosis of the disease. Molecular markers such as metalloproteinases (MMPs), lactate dehydrogenase (LDH), N-Acetyl-ß-D-Glucosaminidase (NAGase), Beta glucuronidase, and glycosaminoglycans (GAGs) are also related to udder disease. Some biomarkers involve proteases that degrade the extracellular matrix, such as metalloproteinases 2 and 9, among others. These proteases are physiologically responsible for the normal remodeling of the extracellular matrix. However, proteases play a preponderant role in the pathophysiology of mastitic processes, especially in their recurrent presentation, with the inhibition of MMPs being an interesting therapeutic proposal. The enzymes LDH, NAGase and beta glucuronidase are indicators of inflammation, since the increase in their activity is associated with leukocyte lysosomal granules. GAGs are constituents of the extracellular matrix and could be used as indicators of mammary health, because they remain constant in milk throughout the productive process of healthy animals and rise in light of mild pathological processes. The analysis and monitoring of markers in dairy cattle could be an important complement to conventional tests for the diagnosis and monitoring of the health of the mammary gland.